Dinamika Organisasi Sosial Islam dalam Pemilihan Gubernur Jawa Tengah - Nugraha, Irwan Abdu; Ifansyah, Muhammad Noor (Prodi Sosiologi Agama, 2019)
Identity politics is a response to political behaviour by a person or group of people who share an identity, such as ethnicity, religion, culture, and gender. Identity politics is also often related to discourse (issue, language, imagery, or other communication expressions) to be used as one of the instruments for the political elite, which is usually done in the electoral arena. Identity politics always emphasizes the interests of its group, in the political identity of tribes and ethnicity to be an important role as a symbol of culture that has its own potential and gives strength in conducting political action. Using a qualitative analytical approach, this paper tried to see the position of one of the Islamic-based community organizations in the election governor and deputy governor of Central Java. The association between NU as a religious social organization with the process and political reality is happening. This paper essentially shows that Islamic Community organizations has evolved into a religious social organization that has increasingly dynamic and open political minds and attitudes. But NU’s political position is culturally welcome NU citizens to be active in any practical political activity but NU insists that it does not reflect the NU movement institutionally an individual movement.